ผลของขนาดอนุภาคและปริมาณสารตัวเติมต่อสมบัติทางกายภาพและสมบัติเชิงกลของยางธรรมชาติที่ผ่านการวัลคาไนซ์ - โอบเอื้อ อิ่มวิทยา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Studies effects of particle size and quantity of carbon black (N330, N550 and N660) and calcium carbonate fillers on physical and mechanical properties of the natural rubber STR 5L used as engine mounts. It was found that the optimum properties of the products can be achieved by using carbon black N330 which has the particle size. For this reason, calcium carbonate was incorporated with carbon black N330 in order to reduce the production cost. By considering both physical and mechanical properties, it can be concluded that the most appropriate ratio between carbon black N330 and calcium carbonate in making engine mounts is 45/15 phr.